Noise Levels in Malaysia Primary Schools: Are We Meeting the International Standards? - Ismail, Noraidah; Karim, Khairani
Noise is increasingly becoming a problem in schools and affects the audibility of speech. The effects of noise hamper learning opportunities for students. Noisy classrooms affect students’ academic performance and wellbeing. Studies have shown that children perform more poorly in noisy situations compared to adults. The current study was done to measure noise levels in classrooms in primary schools in Kuantan. A total of 31 classrooms from eight residential primary schools were selected as the place of study. The noise levels were measured using a sound level meter (SLM) in occupied and unoccupied conditions. On-site observations and checking were done and documented in each school and classroom. The results showed that the noise levels of occupied and unoccupied classrooms were higher than the values recommended by the World Health Organization (WHO) which are 35 dB(A) and 55 dB(A) respectively. The findings showed that the measured noise levels in the classrooms were high enough that it might interfere with the effectiveness of teaching and learning among students and teachers. The source of noise was mainly from the students’ activities in the classes. The current study discusses a few possible suggestions to improve the classroom acoustics.
Keywords: BE:LMIC; BE:RELEVANT; ⛔ No DOI found